Fabrication of photocatalyst film based on TEMPO-oxidized cellulose nanofiber - Yusnaidar Yusnaidar; Wilda Syahri; Harizon Harizon; I Putu Mahendra (Pascasarjana Universitas Negeri Medan, 2023)
The powerful performance of TiO2 and its doped as photocatalyst material initiated the finding of new technique that efficient and effective to degrade the organic pollutant, i.e., azo dyes. This study examined photocatalyst film's photoactivity, TEMPO-oxidized cellulose-containing N-TiO2 (TOC/N-TiO2), on the degradation of azo dyes. TEMPO-oxidized cellulose, which has a negative charge, was sequentially mixed and stirred in the suspension of TiO2 and doped TiO2. This experiment utilized several instruments to determine the physicochemical properties of the photocatalyst film. The UV-DRS and diffractogram data confirmed the anatase phase as the only phase found in N-TiO2, which has a lower bandgap value than the anatase TiO2. These data demonstrated the superior photocatalytic of TOC/ N-TiO2 against azo dyes.Keywords: Doped-TiO2; Film; Photocatalyst; TEMPO-oxidized cellulose nanofiber